TEMPORAL VARIATIONS OF LENGTH, WEIGHT AND CONDITIONFACTOR OF MYSTUS GULIO (HAMILTON, 1822) IN THE INDIAN SUNDARBANS: A POLYNOMIAL REGRESSION APPROACH - RAY, ARCHISMAN; JANA, SUSMITA; MAJUMDER, POONAM; MALAKAR, PRADYUT; PAUL, LITON; PAUL, SANATAN; SADHUKHAN, RANI; JOHNSON, CANCIYAL; LIANTHUMLUAIA; CHANU, THANGJAM NIRUPADA; DAS, BASANTA KUMAR (Journal of the Inland Fisheries Society of India, 2024)
A study was conducted to understand the temporal variation of Mystus gulio (Hamilton, 1822) based on length (cm) and weight (g) collected from River Matla in the Indian Sundarbans. Length-weight relationship (LWR) was determined using the equation W = aLb for 614 fish collected from July 2023 to October 2024. The value of the regression coefficient (b) was estimated to be 3.37 (r2=0.96) for combined sexes and was found to be highly significant (P<0.01) and thus suggesting positive allometric growth. The catfish exhibited its highest body weight in April 2024, averaging 67.61±4.44 g, while its lowest average was in July 2023, weighing 27.06±8.94 g. The mean monthly relative condition factor (Kn) varied from 0.85 to 1.68, with the highest in April (1.68±0.25), suggesting favourable growth during the period. Further, a polynomial regression model between length, weight and condition factor was established which indicated approximately 95% of the variance in the dependent variable (r2 = 0.95). The study will provide valuable insights into determining the population structure of M. gulio and will play a key role in their management on the river Matla.